Pengaruh Media Pembelajaran Berbasis Teknologi terhadap Peningkatan Minat Belajar Siswa Kelas IV di MIN 1 Kutai Timur (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This research is a quantitative research using a phenomenological approach. Research that uses a systematic approach to collect, analyze and interpret numerical data obtained directly from the field. This study uses data collection techniques in the form of observation techniques, questionnaires and documentation. The population in this study were 50 respondents of class IV E and IV F students of MIN 1 East Kutai. Furthermore, to analyze the data, the researcher used a simple linear regression formula with validity and reliability test calculations and assisted by using the IBM SPSS 2.6 application. From the calculation results, it was found that the results that influenced technology-based learning media on increasing student learning interest were 0.307 with an interval category between 0.200-0.390 which means having a low correlation level so that it can form a regression equation Y = 46.358 + 0.277X. The results of the hypothesis that were tested using the t test obtained results of 2.146> 2.010 or tcount> ttable, so it can be stated that Ha is accepted and Ho is rejected. Based on the results of t count, it can be concluded that there is a significant relationship or influence between the independent variables on the dependent variables. Thus, the Influence of Technology-Based Learning Media on Increasing Learning Interest in Grade IV Students at MIN 1 Kutai Timur has a positive value with a determinant coefficient of 9.42% and 90.58% is influenced by other factors such as learning models, teacher motivation, school environment, and parental guidance.